2008
DOI: 10.1128/aac.00017-08
|View full text |Cite
|
Sign up to set email alerts
|

Detection of New arr-4 and arr-5 Gene Cassettes in Clinical Pseudomonas aeruginosa and Klebsiella pneumoniae Strains from Brazil

Abstract: New arr alleles emerged in class 1 integrons from a clinical Pseudomonas aeruginosa strain (arr-4) and four Klebsiella pneumoniae strains (arr-5) in Brazil/American continent. arr-4 was preceded by aacA7-catB3, whereas arr-5 was the unique cassette. The putative proteins shared 75% (Arr-5) and 78% (Arr-4) identities with Arr-2.Rifampin resistance is a notable global health problem concern (11), since it is the front line drug for treating tuberculosis (4) and preventing meningococcal diseases (13). More than 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…The aacA4 gene cassette was present in both integrons, but they carried two different ␤-lactamase genes, bla OXA-35 and bla PSE-1 . The integron in isolate K34-73 also carried a new putative arr gene (named arr-7), encoding rifampin resistance, that was most similar to the Arr-4 gene (90% amino acid identity; GenBank accession number EF660562) (5).…”
Section: Origin Of Isolatesmentioning
confidence: 99%
“…The aacA4 gene cassette was present in both integrons, but they carried two different ␤-lactamase genes, bla OXA-35 and bla PSE-1 . The integron in isolate K34-73 also carried a new putative arr gene (named arr-7), encoding rifampin resistance, that was most similar to the Arr-4 gene (90% amino acid identity; GenBank accession number EF660562) (5).…”
Section: Origin Of Isolatesmentioning
confidence: 99%
“…Here, we observed that this H-Y-[QED] motif is highly conserved in almost all hundreds of Arr sequences analyzed, indicating its importance in Arr activity, and suggesting that these Arr sequences could be functional. Indeed, the Arr enzymes already functionally characterized (Arr-ms, Arr-2 to Arr-8, Arr-cb, Arr-sc, Arr_Mab, Arr-wd1-4) 2 , 4 , 6 8 and those of the present study were observed along the phylogenetic tree, showing that despite the sequence diversity, even in the RIF binding sites, their activities against rifamycins are maintained. These patterns were observed in sequences carried by bacteria belonging to high and low antibiotic-impacted environments.…”
Section: Discussionmentioning
confidence: 49%
“…Highly conserved residues (≥ 90%), considering all Arr sequences analyzed in the phylogeny, are represented below the alignment by the fuchsia blocks. References: Arr-2, Arr-sc, and Arr-ms 1 ; Arr-4 and Arr-5 6 ; Arr-8 8 ; Arr-w1, Arr-w2, Arr-w3, and Arr-w4 4 ; ArrMab 7 ; Arr-cb 2 . …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1b ). Our results include the rifampin and NAD + binding sites reported in the previous studies of arr-ms from Mycobacterium smegmatis , arr-sc from S. coelicolor , and arr-2 and homologous genes ( arr -3, arr- 4, arr- 5, arr -7, and arr -8) from several gram-negative pathogenic bacteria 13 , 43 46 . In particular, H19 and Y49, which were identified for NAD + binding 13 , were highly conserved in our alignment.…”
Section: Resultsmentioning
confidence: 58%